(untitled) (NTU Journal of Agriculture and Veterinary Science, 2023)
Abstract The study was conducted in the sheep field of (Kosar) company in the Kalk district. It was conducted to determine the effect of adding slow-release urea to the concentrated diet gradually instead of fast-release urea in an attempt to improve the efficiency of feed utilization , improve rumen conditions, and its reflection on the productive performance and some blood biochemical indices of Awassi ewes milk. 24 heads of newly parented ewes aged between 3-4 years distributed to four groups was the sample. It has fed onthe same concentrated diet. The first group treated with 1.5 urea only and the second Treated with 1 % urea and 0.6 % slow-release urea .The third Treated with 0.5 % urea and 1.2 % slow-release urea and the fourth Treated with 1.8 % slow-release urea only .The study took two months, from the birth of ewes until weaning lambs, with a Completely Randomized Design. The total average weight gain for ewes was (8.37, 9.72, 6.74, 5.67) kg, and through the results, it was observed that there is a positive effect of adding Menogen to Awassi ewes feeds in the average daily and total milk production as the fourth treatment significantly (P?0.05) exceeded the rest of the treatments. The percentage of fat, protein and lactose in milk alsohas significantly (P?0.05) exceeded in the fourth treatment than the rest of the treatments, no significant difference was observed between treatments in total blood protein concentration albumin and globulin . But blood urea concentration was significant increase (P?0.05) in favor of fourth treatment and first one compared to first treatment computationally with third, plasma cholesterol concentration increased significantly (P?0.05) with increasing level of slow-release urea in third treatment compared to other treatments, triglycerides concentration in blood decreased significantly (P?0.05) with increasing level of slow-release urea for third treatment and fourth one compared to first one computationally with second. Blood enzyme ALT was significantly increased (P?0.05) in third treatment followed by fourth treatment and first one compared to second, AST enzyme decreased significantly (P?0.05) in third treatment compared to first one and second one computationally with fourth.